Ethidium bromide changes the nuclease-sensitive DNA binding sites of the antitumor drug cis-diamminedichloroplatinum(II). - Tullius, T D (1982)
Exonuclease III has been shown previously to reveal the binding sites of the antitumor drug cis-diamminedichloroplatinum(II) on DNA. Pretreatment of the same DNA with the intercalator ethidium bromide causes new platinum binding sites to be detected by the exonuclease III method. In particular, a 5'd(G6-D-G2)3' sequence in a 165-base-pair restriction fragment of plasmid pBR322 becomes a preferred site for exonuclease III-detectable cis-diamminedichloroplatinum(II)binding. This switching of nuclease-sensitive platinum binding to new sites by the influence of another drug, ethidium bromide, offers an explantation at the molecular level for the phenomenon of synergism in combination chemotherapy.